Childhood physical abuse and emotional neglect are specifically associated with adult mental disorders. (3rd July 2020) - Salokangas, Raimo K. R.; Schultze-Lutter, Frauke; Schmidt, Stefanie J.; Pesonen, Henri; Luutonen, Sinikka; Patterson, Paul; Graf von Reventlow, Heinrich; Heinimaa, Markus; From, Tiina; Hietala, Jarmo
Abstract: Background: Childhood adversities and trauma (CAT) are associated with adult mental disorders. Nevertheless, although CAT of different domains mostly co-occurs, and co-morbidity is common, the associations between CAT and mental disorders, when taking these interrelations into account, are not well known. Aims: We aimed to study differential associations between the five core domains of CAT and current axis-I disorders, taking into consideration their interrelations. Methods : Four hundred and fifteen outpatients attending adult primary ( n = 255) and psychiatric care ( n = 160) were assessed with the Trauma and Distress Scale (TADS) and the Mini International Neuropsychiatric Interview (MINI). Associations between CAT core domains and diagnostic categories were examined by path analyses. Results: At least some infrequent experience of CAT (83.6%), mostly of neglect, and current mental disorders (49.4%), mostly depression, was frequent, as were co-morbidities and co-occurrence of CAT domains. Considering these interrelations in a path model of excellent fit, physical abuse predicted depressive, manic, psychotic and anxiety disorders, whereas emotional neglect predicted depressive, anxiety and substance misuse disorders. Conclusions: Of all five CAT core domains, physical abuse and emotional neglect had the strongest association with adult psychiatric disorders and might have transmitted earlier reported main effects of other CAT domains onto mental disorders.